2022
DOI: 10.3390/su14116399
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Influence of Machine Translation: Perceptions and Attitudes of Translation Instructors and Learners in Hong Kong

Abstract: In this era of globalisation, translation technologies have become more popular in daily communication, the education sector, and the translation industry. It is observed that there is a prevalent use of machine translation (MT) among translation learners. The proper use versus abuse of MT can be a critical issue regarding its role in and impact on translation teaching. This exploratory study aims at investigating learners’ and instructors’ knowledge of MT, experience in MT use, perceived MT quality, ethics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…However, they may still be concerned about some TT flaws: for instance, producing various errors and unnatural expressions, impeding the selection efficiency, or undercutting their creativity, etc. ( Briggs, 2018 ; Liu et al, 2022 ; Rico and Gonzalez Pastor, 2022 ). These mixed perceptions may contribute to their belief that translation technology is only slightly effective for their translation, and they should be cautious of it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they may still be concerned about some TT flaws: for instance, producing various errors and unnatural expressions, impeding the selection efficiency, or undercutting their creativity, etc. ( Briggs, 2018 ; Liu et al, 2022 ; Rico and Gonzalez Pastor, 2022 ). These mixed perceptions may contribute to their belief that translation technology is only slightly effective for their translation, and they should be cautious of it.…”
Section: Discussionmentioning
confidence: 99%
“…However, the existing literature predominantly emphasizes the course design itself, painting an impersonal picture of students as the recipients. Little research has investigated the human factors associated with students’ translation technology learning and use, such as their attitudes ( Liu et al, 2022 ). In fact, attitudes, which gain universal recognition as a critical factor in students’ acceptance of technologies ( Vandewaetere and Desmet, 2009 ; Zarrinabadi et al, 2022 ), are very much related to the degree to which TTT is successful ( Alcina et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Such technological advancements have led to more sophisticated and efficient language and translation systems than ever before, which are proving to be a powerful tool for improving translation performance. 48 The capability to employ such tools has become a critical skill that associates with other competences to promote translation proficiency. 49 This transition has been a significant change in the field of translation, allowing more efficient and effective translation practices.…”
Section: Translation Technology Competencementioning
confidence: 99%
“…53 The widespread application of machine translation in educational endeavors showed that machine translation has contributed to the growth and acquisition of students' translation competence. 48 It increases students' knowledge of the source and target languages and their ability to transfer information between them. 54…”
Section: Machine Translationmentioning
confidence: 99%
See 1 more Smart Citation